Optimizing Financial Literacy and Financial Inclusion through Fintech Education for Vocational School Students - Raya Puspita Sari Hasibuan; Marlya Fatira AK; Amelira Haris Nasution; Khairani; Vivianti Novita; Fachmi Ridho (CSR International Journal, 2024)
Financial Literacy and Financial Inclusion Optimization Through Fintech Education in Vocational School Students is done precisely at Al-Washliyah 2 Private Vocational School, Jl. Stadium No. 2, Trading, Bandar District, Simalungun Regency Aims to provide an understanding of financial literacy towards the use of fintech which includes topics such as Definition of Financial Literacy, Importance of Financial Planning, Definition of Fintech, Difference between Legal Fintech and Illegal Fintech, Types of Fintech, The Importance of Understanding Fintech, Definition and Function of the Financial Services Authority (OJK) towards Fintech. The school has never received education related to this material from any party. To run PMKM activities smoothly, the service team carried out data collection techniques by interviewing the Al-Washliyah 2 Commerce Private Vocational School. The solution is to provide knowledge transfer through the Financial Literacy Seminar on the Use of Fintech. The cost of implementing PMKM activities is Rp—1,270,000 (one million thirty-one thousand five hundred rupiah). After carrying out community service activities in the form of training and seminars for students, the results of the service were obtained that Low Financial Literacy Against the Use of Fintech has been overcome with educational activities such as providing financial literacy education on the use of fintech which includes topics such as Definition of Financial Literacy, The Importance of Financial Planning, Definition of Fintech, Difference between Legal Fintech and Illegal Fintech, Types of Fintech, The Importance of Understanding Fintech, the Definition and Function of the Financial Services Authority (OJK) towards Fintech. This successful activity formed students' knowledge and skills about Financial Literacy Towards the Use of Fintech to reach an average score of 88.55% with a maximum knowledge of 98.20% for all participants. The absence of an educational program that specifically discusses the importance of Financial Literacy for the Use of Fintech, which also supports social science lessons in the context of economic life activities, is a challenge that needs to be overcome. To overcome this problem, 3 students have been presented who better understand Financial Literacy Towards the Use of Fintech. These 3 students are expected not only to provide an understanding to their peers about the importance of understanding related to financial literacy and fintech but also to encourage students to be more careful in managing finances and choosing fintech applications. With an interesting and creative approach, it is hoped that students can disseminate this knowledge more widely, creating awareness among students about the shared responsibility in maintaining and managing finances. Keywords: Financial Literacy; Fintech; Vocational High School; Financial Inclusion.